Augmented Reality Flashcards to Improve Early Literacy in Indonesian Primary Schools - James Njoroge; Wang Jing; Zhang Li (Yayasan Adra Karima Hubbi, 2025)
Background. Early literacy development is a crucial foundation for lifelong learning, yet many Indonesian primary school students continue to face difficulties in recognizing letters, decoding words, and connecting phonemes to visual symbols. Traditional flashcards, while useful, often fail to sustain young learners’ attention or provide interactive engagement. Purpose. This study aims to examine the effectiveness of AR-based flashcards in improving early literacy skills among first-grade students in Indonesian primary schools. Method. Employing a quasi-experimental design, the study involved 60 students divided into an experimental group using AR flashcards and a control group using conventional printed flashcards over six weeks. Data were collected through pre- and post-literacy assessments and classroom observations. Results. Statistical analysis using paired-sample t-tests indicated a significant improvement in letter recognition, word decoding, and reading fluency among the experimental group (p < .05). Observational findings also revealed heightened motivation, concentration, and active participation when AR elements were integrated into literacy instruction. Conclusion. The study concludes that AR flashcards provide a powerful medium for enhancing foundational literacy through multisensory engagement and interactive learning. The findings highlight the potential of AR technology to enrich early childhood education and support Indonesia’s national efforts in promoting digital-based learning environments.